Porcine Detection on Anti-Covid 19 Immunity Gelatin Capsules Sold at Market X in North Surabaya Using Quartz Crystal Microbalance (QCM) Sensors - Syukrianto, Syukrianto; Umarudin, Umarudin; Madurani, Kartika Anoraga; Kurniawan, Fredy (Universitas Negeri Semarang, 2021)
Immune gelatin capsules, which have not been fully indicated on the packaging, need to be investigated porcine or bovine using a Quartz crystal microbalance (QCM) tool. The advantages of the QCM tool are sensitivity to the crystal oscillation frequency at a specific temperature, humidity, pressure, speed, and vibration, which will make this piezoelectric oscillator used as a sensor with a high accuracy level. The purpose of this study was to determine the content of porcine (pork) or bovine (beef) in anticovi19 immunity gelatin capsules sold at market X, North Surabaya. The method used to distinguish pork gelatin and beef gelatin is a Quartz crystal microbalance (QCM) tool. In this study, the detection of anti-covid19 immunity gelatin capsules was carried out using a QCM tool. This research method was carried out in a factual experimental manner, and sampling with the quota technique was 3 grams for each sample with a different brand. The results of research conducted on four samples with other brands originating from the market X area of North Surabaya showed the detection results of 2 samples with adverse effects (-), and two samples with positive results (-), meaning that the negative samples contained beef gelatin (bovine) and the positive sample contains pork (porcine). A decrease in frequency characterized the sample of immunity gelatin capsules containing bovine gelatin. In contrast, the sample of immunity gelatin capsules containing porcine gelatin was characterized by increased frequency.